(untitled) (Journal of Dhaka Medical College, 2010)
In this paper the remnants of British medical jurisprudence, the medico legal service of Bangladesh were discussed to improve the current medico legal practice and to propose future plan. In Bangladesh, all unnatural deaths are to be reported at the nearest police station and an appointed police officer should visit the scene of occurrence for investigation and to arrange postmortem if required. The forensic services of the country are delivered partly by academic staffs of government medical colleges’ forensic medicine department and rest by the civil surgeons - the district health administrator. The civil surgeons perform postmortem by the doctors under him in district hospitals, most of them have no forensic qualifications. Currently academic and professional postgraduate courses are available. The chemical examiner’s laboratory is situated at Dhaka with the facility of quantitative tests only. The Government of Bangladesh is trying to standardize the existing system. A workshop on medico legal service was organized recently at Dhaka by the Medico Legal Society of Bangladesh. A DNA profiling laboratory was established at Dhaka Medical College Forensic Medicine Department. Such progress is a milestone in the development of medico legal service in Bangladesh. However, with a few exceptions teaching and training facilities are still lacking. Key words: Forensic; Bangladesh Perspective. DOI: 10.3329/jdmc.v19i1.6255 J Dhaka Med. Coll. 2010; 19(1) : 61-64.